As primeiras interpretações marxistas da realidade brasileira - Del’Omo Filho, Rafael [UNESP] (2014)
This thesis aims to present the first three Marxist interpretations about the Brazilian reality and their interconnection, their commonalities and differences. We start from some initial considerations of the author of this dissertation comprehension about the Brazilian development until the period of the works studied and the situation in the international division of Marxism and its influence on such works. Interpretations analyzed refer to Octavio Brandão, author of Agrarianism and Industrialism - Marxist-Leninist Essay on the revolt of St. Paul and the War of Classes in Brazil, in which there is a first attempt to understand Brazil using some concepts of materialist historical methodology; those produced by the Communist League (Internationalist Communist League later) , Brazilian section of the International Left Opposition lead by Leon Trotsky , and finally the consecrated work of Caio Prado Junior , responsible for the major interpretation of Brazilian past colonial. We stick with particular emphasis on the last two because of its proximity in analyzing and greater analytical rigor used and its programmatic differences. As expected from the historical materialism, their analysis is not limited to pure abstract understanding, but they serve to substantiate their practical action, element in the three interpretations addressed here. In the final conclusions , weave brief comparisons between those works in character synthesis of the foregoing throughout the dissertation as well as the author's own views on this topic.